Staff Attendance System using RFID - Muhammad Thariq Abdul Razak; Chuah Chai Wen (Society of Visual Informatics, 2017)
Attendance system University Tun Hussien Onn Malaysia is the system to record, and monitor the staff attendance to the daily work. This project is to design develop and implement attendance system using radio frequency identification technology. This technology is divided into two types which are system passive and system active. The proposed system used the system passive to record staff attendance. Frequency identification technology will read the staffs tag and the attendance are recorded automatically and store it in database. The proposed system has several securities feature that can prevent security breaches which is captcha and audit trail. The advantage of proposed system is can differentiate between the human input and robot input and record all the user activity when access to the system.